2019
DOI: 10.1007/s10495-019-01557-5
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal life or death linked to depression treatment: the interplay between drugs and their stress-related outcomes relate to single or combined drug therapies

Abstract: Depression is a serious medical condition, typically treated by antidepressants. Conventional monotherapy can be effective only in 60–80% of patients, thus modern psychiatry deals with the challenge of new methods development. At the same moment, interactions between antidepressants and the occurrence of potential side effects raise serious concerns, which are even more exacerbated by the lack of relevant data on exact molecular mechanisms. Therefore, the aims of the study were to provide up-to-date informatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 53 publications
3
16
0
Order By: Relevance
“…In our study, following in vitro fluoxe2ne treatment with 10µM for 24 hrs, we observed an overall reduc2on in the propor2on of G2/M phase cells but there was no difference on the effects of fluoxe2ne between the cases and control lines. These findings are similar to other studies (Lin et al, 2016;Solek et al, 2019), however, the reason why we could not observe differences in other phases especially G0/G1 might be due to short dura2on of fluoxe2ne exposure. A higher concentra2on for longer dura2on may be needed for these effects to occur (Brei€eld et al, 2016;Brei€eld, Scholl, Steffens, Laje, & S2ngl, 2017;Morag et al, 2010).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In our study, following in vitro fluoxe2ne treatment with 10µM for 24 hrs, we observed an overall reduc2on in the propor2on of G2/M phase cells but there was no difference on the effects of fluoxe2ne between the cases and control lines. These findings are similar to other studies (Lin et al, 2016;Solek et al, 2019), however, the reason why we could not observe differences in other phases especially G0/G1 might be due to short dura2on of fluoxe2ne exposure. A higher concentra2on for longer dura2on may be needed for these effects to occur (Brei€eld et al, 2016;Brei€eld, Scholl, Steffens, Laje, & S2ngl, 2017;Morag et al, 2010).…”
Section: Discussionsupporting
confidence: 93%
“…Previous studies have shown fluoxe2ne to cause an arrest in the G0/G1 phase in various cell lines (Hoose et al, 2012;Krishnan et al, 2008;Serafeim et al, 2003) along with reduc2on of cells in the G2/M and S phase (Lin et al, 2016;Solek et al, 2019). Some studies have shown these effects ini2ally at 24 hrs with 10µM dose of fluoxe2ne, which is the reason for considering this dose and 2me for our study.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Depression and anxiety disorders are highly prevalent and disabling diseases that cause cognitive impairment within the patient’s lifetime (Solek and others 2019). Increasing evidence has shown that Wnt/β-catenin signaling is associated with depression disorders through the regulation of neurogenesis (Lie and others 2005; Sani and others 2012; Tayyab and others 2018).…”
Section: Wnt/β-catenin Signaling In Neural Stem Cell Homeostasismentioning
confidence: 99%
“…In vitro neuronal cell culture system, amitriptyline does not cause cytotoxicity up to 20 μM (Fig. 1 ) and IC 50 for cell proliferation is reported to be 35.59 ± 3.48 μM 60 . To evaluate whether amitriptyline accumulation through long-term and/or high-dose use could be associated with the increased risk of neurodegenerative disease, we used relatively high concentrations in this study.…”
Section: Discussionmentioning
confidence: 91%